Time flies [compact disc] - Lauderdale, Jim (Yep Roc Records, 2018)
Jim Lauderdale's 31st album is a return to what he does best: classic country infused with striking notes of Americana and soul. As a two-time Grammy winner and multi-genre dabbler, Lauderdale is able to carve out space for himself in music worlds both familiar and foreign, and after a creative legacy spanning nearly three decades, it's no surprise that his ability to rejuvenate his sound is indomitable.